USING THE CASE METHOD IN TEACHING CHEMISTRY - Ruziev I. Kh.; Ergashev E. Yu.; Erkinova G. A.; Salimova G. B. (Scholars Digest Publishing, 2023)
It is known that the main goal of the modern pedagogy in its development is to train specialists, those who have information and communication technologies that allow the application of fundamental knowledge, fundamentals of project activities in solving specific professional problems, suggestions as a method of progressive pedagogical technology. The article describes the activity training during the practical training of the "Organic Chemistry" course for students in the directions of the pedagogical experience described in the article. The use of the case method activates students' cognitive activity, develops motivation for learning, and ensures the correctness of the saying that practice without theory, and theory without practice, is meaningless.
Keywords: work method, higher engineering education system, state method, state, state technologies, application methodology, case method, organic chemistry, synthesis gas, ethanol, insecticide, pesticide, anesthetic, rules, orientation in the benzene ring.